EXTRACTION, PHYTOCHEMICAL SCREENING, TOTAL PHENOLIC CONTENT, AND ANTIBACTERIAL ACTIVITY OF MISTLETOE ON OIL PALM (Ficus heteropleura Blume) LEAVES - Hamiro, Fauzia; Perdana, Fitra; Syahri, Jufrizal (Lantanida Journal, 2025)
Ficus heteropleura Blume, commonly known as mistletoe on oil palm, is a semi-parasitic plant that grows on oil palm trees. This study aimed to investigate the secondary metabolite profile, determine of total phenolic content, and evaluate antibacterial activity of ethyl acetate extract of F. heteropleura leaves. Extraction was performed using a grade maceration method. Qualitative phytochemical screening was conducted to identify major classes of secondary metabolites, and total phenolic content was quantitatively determined using the Folin–Ciocalteu method with gallic acid as the standard. Ethyl acetate extraction yielded 19.27 g of crude extract. Phytochemical analysis revealed the presence of steroids, flavonoids, saponins, and tannins. The total phenolic content was determined to be 35.730 mg GAE/g. UV-Vis spectrophotometric analysis showed characteristic absorption peaks at 475.0 nm and 432.8 nm, indicating the presence of phenolic pigments with conjugated C=O groups and a peak at 666.3 nm associated with chlorophyll, contributing to the green coloration. FTIR analysis confirmed the presence of functional groups such as O–H, C≡C, C=O, C=C, and C–O. Antibacterial activity demonstrated that the ethyl acetate extract exhibited strong inhibitory effects against Staphylococcus aureus and Escherichia coli, with average inhibition zone diameters ranging from 5 to 10 mm, indicating strong antibacterial activity.